Gas separation properties of functionalized carbon nanotubes mixed matrix membranes - Mohd. Sanip, Suhaila (Pergamon Press, 2011)
The synergistic combinations of organic polymers for separation applications with inorganic substances such as multi-walled carbon nanotubes (MWNTs), have resulted in a new class of membrane material called mixed matrix membrane (MMM) for the separation of CO2/CH4 gases. Mixed matrix membrane incorporated functionalized MWNTs (f-MWNTs) were fabricated by the solution casting method, in which the f-MWNTs were embedded into the polyimide membrane and the resulting membranes were characterized. The effect of nominal MWNTs content between 0.5 and 1.0 wt% on the gas separation properties was investigated. The mixed matrix membranes showed 100% enhancement for the selectivity of CO2/CH4 compared to the corresponding neat polymer membrane. This new class of mixed matrix membrane has the ability to separate gases at the molecular level and has the potential to ultimately reduce the energy consumed in present-day separation operations. This study has shown that addition of CNTs to polymeric membranes has improved separation properties of the membranes to a certain extent.